2015
DOI: 10.3892/ijmm.2015.2284
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human telomerase reverse transcriptase mediates the senescence of mesenchymal stem cells through the PI3K/AKT signaling pathway

Abstract: Multipotent mesenchymal stem cells (MSCs) are widely used as seed cells in studies of tissue engineering and regenerative medicine; however, their clinical application is limited due to replicative senescence. It has been demonstrated that telomerase expression extends the lifespan and maintains the bone-forming ability of MSCs; however, the detailed role and the underlying molecular mechanisms in MSCs remain largely unknown. In the present study, we found that senescence was associated with human telomerase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…42,43 Human telomerase reverse transcriptase elongates and stabilizes telomeres, alleviating replicative senescence and apoptosis. 44 In our study, E2 treatment increased the expression of hTERT in hPDLSCs and prevented cellular senescence (Figures 2 and 5), which suggests that E2 modulate hTERT to maintain hPDLSCs stemness. Sox2, Oct4 and c-Myc are critical stemness-related genes that maintain pluripotency and self-renewal of embryonic stem cells.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…42,43 Human telomerase reverse transcriptase elongates and stabilizes telomeres, alleviating replicative senescence and apoptosis. 44 In our study, E2 treatment increased the expression of hTERT in hPDLSCs and prevented cellular senescence (Figures 2 and 5), which suggests that E2 modulate hTERT to maintain hPDLSCs stemness. Sox2, Oct4 and c-Myc are critical stemness-related genes that maintain pluripotency and self-renewal of embryonic stem cells.…”
Section: Discussionsupporting
confidence: 62%
“…During MSC proliferation in vitro, a decrease in telomere length correlates with the loss of cell viability, suggesting that telomere length and telomerase activity are indispensable for the stemness maintenance . Human telomerase reverse transcriptase elongates and stabilizes telomeres, alleviating replicative senescence and apoptosis . In our study, E2 treatment increased the expression of hTERT in hPDLSCs and prevented cellular senescence (Figures and ), which suggests that E2 modulate hTERT to maintain hPDLSCs stemness.…”
Section: Discussionsupporting
confidence: 58%
“…Numerous studies demonstrated the pro-senescence activity of the Akt signaling pathway [36-38]. However, the anti-senescence activity of the Akt signaling pathway has also been proposed in several types of tissues and cells, such as multipotent mesenchymal stem cells [39]. In our study, GLP-1 suppressed HG/HL-induced Akt activation (Fig.…”
Section: Discussionmentioning
confidence: 47%
“…Long-term expansion of MSCs is reflected by telomere attrition, since they have insufficient telomerase activity to overcome the progressive telomere erosion [28]. Supporting these findings, overexpression of hTERT in senescent MSCs partially counteracts replicative senescence [29,30]. On the other hand, long-term cultures of human stem cells, including MSCs, have shown several types of chromosomal abnormalities that could compromise genome integrity and their clinical applicability [31,32].…”
Section: Telomere Attrition-a Hallmark For Replicative Senescencementioning
confidence: 49%